2005
DOI: 10.1007/s00431-005-0008-9
|View full text |Cite
|
Sign up to set email alerts
|

Absence of breast-feeding is associated with the risk of type 1 diabetes: a case–control study in a population with rapidly increasing incidence

Abstract: There are indications that the effect of environmental factors on the risk of type 1 diabetes mellitus (T1DM) is increasing over time. This can be documented by the rapid increase of T1DM incidence in genetically stable populations. Our aim was to study an association of T1DM with the variable factors of the perinatal period and of early infancy, using data from children born over a period of changing exposure to some of the studied factors. A case-control dataset was analysed, consisting of 868 diabetic child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 22 publications
2
65
1
1
Order By: Relevance
“…The more general MEDLINE search identified a further eight articles [33][34][35][36][37][38][39][40], and review of reference lists revealed another two articles [41,42].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The more general MEDLINE search identified a further eight articles [33][34][35][36][37][38][39][40], and review of reference lists revealed another two articles [41,42].…”
Section: Resultsmentioning
confidence: 99%
“…This observed increase in diabetes risk after Caesarean section delivery could not be explained by the confounding influence of birthweight, gestational age, maternal age, birth order, maternal diabetes or breastfeeding. Table 1 b Breast-feeding was categorised as breast-feeding at discharge from hospital [18,32], any breast-feeding [15,25,27], breast-feeding for approximately 3 months or more [30,40,43] and breast-feeding for approximately 4 months or more [37][38][39] Ref. cat., reference category…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the different cytokines varied with lactation period. These data can be correlated with the protective effect observed in the study of Malcova et al (2006), where early breast-feeding was shown to provide a greater protection. Therefore, one might hypothesise that early breast milk exposure might lead to an increase in the levels of neonatal cytokines (such as IL2), which, as seen in the hygiene hypothesis, might play a role in the protective action against type 1 diabetes.…”
Section: Breast-feeding Vs Cow's Milk Hypothesesmentioning
confidence: 53%
“…Borch-Johnsen et al (1984) introduced the theory that insufficiency in breast-feeding of genetically susceptible children may lead to the development of b-cell infection and type 1 diabetes. A variety of studies have shown an inverse correlation between a decrease in breast-feeding and the increase in type 1 diabetes risk (Borch-Johnsen et al 1984, Scott 1990, Malcova et al 2006. Human milk seems to contain several molecules and cells that help prevent infection and possibly autoimmunity.…”
Section: Vitamin D Deficiencymentioning
confidence: 99%
“…Short-term breastfeeding followed by early introduction of bovine milk is a known risk factor for type 1 diabetes in infants (Gerstein and VanderMeulen, 1996). The lack of breastfeeding also increases the risk of type 1 diabetes (Malcova et al, 2006) whereas prolonged breastfeeding duration likely reduces the risk of future type 2 diabetes (Stuebe et al, 2005).…”
Section: The Effect Of Breastfeeding On Breast Cancer and Diabetesmentioning
confidence: 99%